The Inhibitory Receptor Siglec-8 Interacts With FcεRI and Globally Inhibits Intracellular Signaling in Primary Mast Cells Upon Activation - Korver, Wouter; Wong, Alan; Gebremeskel, Simon; Negri, Gian Luca; Schanin, Julia; Chang, Katherine; Leung, John; Benet, Zachary; Luu, Thuy; Brock, Emily C.; Luehrsen, Kenneth; Xu, Alan; et al. (Frontiers in Immunology, 2022)
Immunomodulation of mast cell (MC) activity is warranted in allergic and inflammatory diseases where MCs have a central role in pathogenesis. Targeting Siglec-8, an inhibitory receptor on MCs and eosinophils, has shown promising activity in preclinical and clinical studies. While the intracellular pathways that regulate Siglec-8 activity in eosinophils have been well studied, the signaling mechanisms that lead to MC inhibition have not been fully elucidated. Here, we evaluate the intracellular signaling pathways of Siglec-8-mediated inhibition in primary MCs using an anti-Siglec-8 monoclonal antibody (mAb). Phospho-proteomic profiling of FcεRI-activated MCs revealed Siglec-8 mAb-treatment globally inhibited proximal and downstream kinases, leading to attenuated MC activation and degranulation. In fact, Siglec-8 was found to directly interact with FcεRI signaling molecules. Siglec-8 inhibition was dependent on both cytoplasmic immunoreceptor tyrosine-based inhibitory motifs (ITIMs) that interact with the SH2 containing protein phosphatase Shp-2 upon Siglec-8 phosphorylation. Taken together, these data support a model in which Siglec-8 regulates proximal FcεRI-induced phosphorylation events through phosphatase recruitment and interaction with FcεRIγ, resulting in global inhibition of MCs upon Siglec-8 mAb engagement.